Macrophages as Key Drivers of Cancer Progression and Metastasis - Sebastian R. Nielsen; Michael C. Schmid (Hindawi Limited, 2017)
Macrophages are one of the most abundant immune cells in the tumour microenvironment of solid tumours and their presence correlates with reduced survival in most cancers. Macrophages are present at all stages of tumour progression and stimulate angiogenesis, tumour cell invasion, and intravasation at the primary site. At the metastatic site, macrophages and monocytes prepare for the arrival of disseminated tumour cells and promote their extravasation and survival by inhibiting immune-mediated clearance or by directly engaging with tumour cells to activate prosurvival signalling pathways. In addition, macrophages promote the growth of disseminated tumour cells at the metastatic site by organising the formation of a supportive metastatic niche. The development of agents inhibiting the recruitment or the protumorigenic effector functions of macrophages in both the primary tumour and at the metastatic site is a promising strategy to improve cancer survival in the future.